The impact of economic, social and health crises on victims of domestic violence - Andrea Domokos (Belügyi Szemle)
Aim: The situation of victims of domestic violence and partner abuse becomes even more serious in crisis situations. There have been and are ongoing conflicts in the world, which have been scrutinised by economists, sociologists, criminologists, health professionals and lawyers alike in recent years. The latest related research worldwide provides a lot of important new information that can help prepare for the problem and provide professionally competent answers.